Maáyir Ma Ba’d al-Thariqah al-Baidagujiyyah al-Tsalatsah fi Alqurán al-Karim - Hikmah, Hikmah; Hasanah, Mamluatul; Huda, Miftahul (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This research aimed to find the pattern of three parameters of the post method in AlqurÃ¡n. This study adopted qualitative research with a literature review model. The object of this research was a pattern obtained from three post method parameters with al-kalimah al-miftahiyyah in AlqurÃ¡n. The data collection rested upon Qurâ€™anic verses and their interpretations To conduct data analysis, the researchers used content analysis by Klaus Krippendorff. This study revealed the patterns of three parameters of postmethod pedagogy in the Qurâ€™an, such as; particularity from the word â€œhikmahâ€ wisdom which is with the mind and has an understanding as deep research; the parameter of practicality from the words ulul albab as the symbol of deep thinking, ulul abhsar as the symbol of deep feeling, and ulin nuha as the symbol of deep character; and parameter possibility from the word as-shabr as a power in the deep application.